Analysis of Financial Ratios Against Financial Distress in Pharmaceutical Companies - Arnu, Anggi Pasca; Nugraha, Nugraha (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2024)
This research is intended to identify the impact of liquidity, solvency, and profitability ratios on financial distress conditions as measured using the Altman Z-Score model in pharmaceutical sector companies listed on the Indonesia Stock Exchange in the 2019-2022 period, either partially or simultaneously. The analytical method applied involves descriptive analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing using SPSS version 20 software. The implications obtained from this research indicate that, when analyzed partially, the liquidity ratio with the Current Ratio proxy has no effect On financial distress conditions with a significance value of 0.051. The same thing applies to the profitability ratio with the Return On Assets (ROA) proxy with a significance value of 0.838, which is also concluded to not affect financial distress. However, there is a significant negative effect of the solvency ratio with the Debt to Asset Ratio (DAR) proxy on financial distress with a value of 0.015, which means that the higher the DAR will reduce the Altman Z-Score value which is closer to financial distress conditions. These three ratios, liquidity, solvency, and profitability, influence financial distress.